What is the derivative of Tan inverse of x/1+√1-x^2?

1 Answer
Apr 4, 2018

The derivative d/dx[arctan(x/(1+sqrt(1-x^2)))] is equal to 1/(2sqrt(1-x^2)).

Explanation:

I'm not going to include a lot of words in this explanation, since it's mostly just math. There's a lot of special rule usage, but here we go:

color(white)=d/dx[arctan(x/(1+sqrt(1-x^2)))]

Chain rule (derivative of arctan is 1/(1+x^2)):

=1/(1+(x/(1+sqrt(1-x^2)))^2)*d/dx[x/(1+sqrt(1-x^2))]

=1/(1+x^2/(1+sqrt(1-x^2))^2)*d/dx[x/(1+sqrt(1-x^2))]

=1/(1+x^2/(1+2sqrt(1-x^2)+1-x^2))*d/dx[x/(1+sqrt(1-x^2))]

=1/(1+x^2/(2+2sqrt(1-x^2)-x^2))*d/dx[x/(1+sqrt(1-x^2))]

=1/((2+2sqrt(1-x^2)-x^2)/(2+2sqrt(1-x^2)-x^2)+x^2/(2+2sqrt(1-x^2)-x^2))*d/dx[x/(1+sqrt(1-x^2))]

=1/((2+2sqrt(1-x^2)-x^2+x^2)/(2+2sqrt(1-x^2)-x^2))*d/dx[x/(1+sqrt(1-x^2))]

=1/((2+2sqrt(1-x^2))/(2+2sqrt(1-x^2)-x^2))*d/dx[x/(1+sqrt(1-x^2))]

=(2+2sqrt(1-x^2)-x^2)/(2+2sqrt(1-x^2))*d/dx[x/(1+sqrt(1-x^2))]

Quotient rule:

=((2+2sqrt(1-x^2)-x^2)/(2+2sqrt(1-x^2)))*(d/dx[x](1+sqrt(1-x^2))-x*d/dx[1+sqrt(1-x^2)])/(1+sqrt(1-x^2))^2

=((2+2sqrt(1-x^2)-x^2)/(2+2sqrt(1-x^2)))*(1+sqrt(1-x^2)-x*d/dx[sqrt(1-x^2)])/(1+sqrt(1-x^2))^2

=((2+2sqrt(1-x^2)-x^2)/(2+2sqrt(1-x^2)))*(1+sqrt(1-x^2)-x*d/dx[sqrt(1-x^2)])/(1+2sqrt(1-x^2)+1-x^2)

=((2+2sqrt(1-x^2)-x^2)/(2+2sqrt(1-x^2)))*(1+sqrt(1-x^2)-x*d/dx[sqrt(1-x^2)])/(2+2sqrt(1-x^2)-x^2)

=(color(red)cancelcolor(black)(2+2sqrt(1-x^2)-x^2)/(2+2sqrt(1-x^2)))*(1+sqrt(1-x^2)-x*d/dx[sqrt(1-x^2)])/color(red)cancelcolor(black)(2+2sqrt(1-x^2)-x^2)

=(1+sqrt(1-x^2)-x*d/dx[sqrt(1-x^2)])/(2+2sqrt(1-x^2))

Chain rule (derivative of sqrtx is 1/(2sqrtx)):

=(1+sqrt(1-x^2)-x*(1/(2sqrt(1-x^2))*d/dx[1-x^2]))/(2+2sqrt(1-x^2))

=(1+sqrt(1-x^2)-x*(1/(2sqrt(1-x^2))*-2x))/(2+2sqrt(1-x^2))

=(1+sqrt(1-x^2)-x*(-2x)/(2sqrt(1-x^2)))/(2+2sqrt(1-x^2))

=(1+sqrt(1-x^2)+x^2/sqrt(1-x^2))/(2+2sqrt(1-x^2))

=(1+sqrt(1-x^2)+x^2/sqrt(1-x^2))/(2+2sqrt(1-x^2))color(red)(*sqrt(1-x^2)/sqrt(1-x^2))

=(sqrt(1-x^2)+1-x^2+x^2)/(2sqrt(1-x^2)+2(sqrt(1-x^2))^2)

=(sqrt(1-x^2)+1)/(2sqrt(1-x^2)+2(sqrt(1-x^2))^2)

=(sqrt(1-x^2)+1)/((2sqrt(1-x^2))(1+sqrt(1-x^2))

=color(red)cancelcolor(black)(sqrt(1-x^2)+1)/((2sqrt(1-x^2))color(red)cancelcolor(black)((1+sqrt(1-x^2)))

=1/(2sqrt(1-x^2))

Finally, that's it. Hope this helps!